Neuropathogenesis of Zika Virus in a Highly Susceptible Immunocompetent Mouse Model after Antibody Blockade of Type I Interferon. - Darci R Smith (PLoS Neglected Tropical Diseases, 2017)
Animal models are needed to better understand the pathogenic mechanisms of Zika virus (ZIKV) and to evaluate candidate medical countermeasures. Adult mice infected with ZIKV develop a transient viremia, but do not demonstrate signs of morbidity or mortality. Mice deficient in type I or a combination of type I and type II interferon (IFN) responses are highly susceptible to ZIKV infection; however, the absence of a competent immune system limits their usefulness for studying medical countermeasures. Here we employ a murine model for ZIKV using wild-type C57BL/6 mice treated with an antibody to disrupt type I IFN signaling to study ZIKV pathogenesis. We observed 40% mortality in antibody treated mice exposed to ZIKV subcutaneously whereas mice exposed by intraperitoneal inoculation were highly susceptible incurring 100% mortality. Mice infected by both exposure routes experienced weight loss, high viremia, and severe neuropathologic changes. The most significant histopathological findings occurred in the central nervous system where lesions represent an acute to subacute encephalitis/encephalomyelitis that is characterized by neuronal death, astrogliosis, microgliosis, scattered necrotic cellular debris, and inflammatory cell infiltrates. This model of ZIKV pathogenesis will be valuable for evaluating medical countermeasures and the pathogenic mechanisms of ZIKV because it allows immune responses to be elicited in immunologically competent mice with IFN I blockade only induced at the time of infection.